Evaluation of antimicrobial and antipyretic activity ofmethanolic extract of hedychium coronarium rhizomes - RITU ARORA; AVIJIT MAZUMDER (International Journal of Pharma and Bio Sciences, 2018)
In this study methanolic extract of rhizomes of Hedychium coronarium (H.coronarium) belonging to family Zingiberaceae was evaluated for antipyretic and antimicrobial activity by determining its minimum inhibitory concentration MIC (by checker board method) and zone of inhibition (by cup plate method). This study was designed to evaluate the antimicrobial efficacy of the methanolic extract of the rhizomes of H. coronarium against various diarrhea and dysentery causing drug resistant microorganisms isolated from patients admitted in hospitals. It was evident from the results that the extract was highly active against Shigella boydii, Shigella. soneii, Shigella flexneri, Vibrio cholera, E. coli, S. aureus and K. pneumoniae. The result of determination of zone of inhibition was compared with that of standard drug (Ciprofloxacin). This study has pointed that the extract was highly active against Shigella boydii, Sh. soneii, Shigella flexneri, Vibrio cholera, E. coli, S. aureus and K. pneumoniae. The finding of this study further reinforces the importance of H. coronarium rhizomes in traditional healthcare practice. Further investigation is underway to isolate and purify the bioactive antimicrobial principles for potential development into generic antimicrobial agent